SAE Technical Paper Series 2006
DOI: 10.4271/2006-01-1154
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Clamp Force in Brake-by-Wire Systems: A Step-by-Step Identification Approach

Abstract: If your library has a subscription to these conference proceedings, you may also be able to access the published version via the library catalogue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In our previous works [9], [11], we have shown that the characteristic curve of the e-caliper can be modeled by a thirdorder polynomial. The measurements given by the internal clamp force sensor are modeled as the sum of two parts: the clamping component and the friction component.…”
Section: Characteristic-curve Calibration: Algorithmmentioning
confidence: 99%
“…In our previous works [9], [11], we have shown that the characteristic curve of the e-caliper can be modeled by a thirdorder polynomial. The measurements given by the internal clamp force sensor are modeled as the sum of two parts: the clamping component and the friction component.…”
Section: Characteristic-curve Calibration: Algorithmmentioning
confidence: 99%
“…Applying the defined form of (8) to a new uniform random data set yields a root-mean-square error (rmse) of 0.28 kN. This error is attributed to the model structure of (8), being not entirely representative [19], as well as the sensory-noise effects. Fig.…”
Section: B Compensationmentioning
confidence: 99%
“…Hoseinnezhad et al [7] found that the use of a characteristic curve to estimate clamp force for dynamic scenarios is inaccurate due to the dynamic behaviour of the caliper. The cause of this effect is attributed to the viscoelastic behaviour exhibited mainly by the aluminium caliper bridge [8] and to some degree the brake pads [9].…”
Section: Developmental Backgroundmentioning
confidence: 99%
“…The cause of this effect is attributed to the viscoelastic behaviour exhibited mainly by the aluminium caliper bridge [8] and to some degree the brake pads [9]. To accommodate for this, Hoseinnezhad et al [7] developed a dynamic clamp force estimator that solely relied on position measurements from a resolver. This model is shown in discrete time notation as follows:…”
Section: Developmental Backgroundmentioning
confidence: 99%
See 1 more Smart Citation